A global load balancing strategy for a distributed computer system - Baumgartner, K.M.; Wah, B.W. (Workshop on the Future Trends of Distributed Computing Systems in the 1990s: Proceedings, 1988)
A load-balancing strategy is described for a computer systems connected by a multiaccess broadcast network. The strategy uses the existing broadcast capability of these networks to implement an efficient search technique for finding stations with the maximum and the minimum workload. The overhead of distributing status information in the proposed strategy is independent of the number of stations, eliminating the primary source of overhead in load balancing. An implementation of the strategy on a network of Sun workstations is presented. It consists of two modules that are executed at all participating computers: the distributed-search module that isolates the maximally and minimally loaded computers, and the job-migration module that places a job on the basic of the load extremes.< >